(untitled) (Dhaka University Journal of Pharmaceutical Sciences, 2021)
The present research study was designed to evaluate the effect of zinc supplementation on body weight, serum triglyceride, cholesterol, glucose homeostasis, oxidative stress, and hepatic function in mice. Mice were treated with zinc sulphate at an equivalent weight of 6.5 mg/kg-body weight elemental zinc for four weeks. Bodyweight, serum glucose, triglyceride, cholesterol, serum MDA, nitric oxide, vitamin C, and hepatic enzymes level were determined at the end of the study period. Data from this study showed that supplementation with zinc in mice maintained a balanced blood glucose homeostasis throughout the experimental period. Moreover, treatment with zinc showed a significant (p <0.05) decrease in serum triglyceride and cholesterol level along with a decrease in the body weight compared to control. Treatment with zinc significantly attenuated the rate of lipid peroxidation whereas increased the level of vitamin C and NO level. The protective effect of zinc on liver activity was observed. Treatment with zinc showed a strong negative association with serum total cholesterol (r= -0.934, p = 0.02), triglycerides level (r= -0.709, p = 0.05), and body weight (r= -0.899, p = 0.01). The present findings demonstrate that zinc supplementation can be helpful to maintain a glucose homeostasis, ameliorate hyperlipidemia, oxidative stress, and liver dysfunction. Therefore, zinc supplementation can be suggested to alleviate diseases associated with metabolic syndrome and oxidative stress. Dhaka Univ. J. Pharm. Sci. 20(1): 59-66, 2021 (June)